New minimum infectious level of hepatitis B virus proposed and continued testing for HBsAg questioned - McCullough, Jeffrey (Annals of Blood, 2018)
The factors involved in transmission of infection from transfusion are: (I) circulating level of infectious agent; (II) binding of virus to neutralizing antibody in the donor; (III) stage of infection in the donor; (IV) particular blood component transfused; (V) storage duration of infected RBCs; (VI) degree of immunosuppression in the recipient; and (VII) blood volume of the recipient (1). Thus, the level of circulating infectious agent in the donor is important but only one factor in determining the likelihood of infection transmission from a particular unit of blood (1). While a considerable amount of data is available related to infectivity of different levels of circulating virus, a wide range of levels is reported.